High-strength hard alloy cutter base material and preparation method thereof
Through nickel coating layer, alloy component optimization and functional coating treatment, the problem of insufficient sintering and mechanical properties of WC-Ni cemented carbide is solved, and a cemented carbide tool matrix material with high strength, excellent wear resistance and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202510622460.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-06-13
- Estimated Expiration
- 2045-05-15
AI Technical Summary
The sintering and mechanical properties of the existing WC-Ni carbide are poor, resulting in insufficient wear resistance and average corrosion resistance.
Tungsten carbide is treated with a nickel precursor solution to form a nickel coated layer, and combined with lanthanum powder, chromium carbide and MXene materials, the adhesion and density are improved by modified silica sol and ball milling. At the same time, functional coatings are sprayed and heat treated to form an organic-inorganic three-dimensional crosslinking network to improve surface wear resistance and corrosion resistance.
The sintering, mechanical properties, wear resistance and corrosion resistance of cemented carbide are significantly improved, forming a high-strength carbide tool matrix material with excellent comprehensive performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cemented carbide tools, and more specifically, to a high-strength cemented carbide tool matrix material and a preparation method thereof. Background Art
[0002] Cemented carbide is an alloy material made of refractory metal hard compounds and binding metals through powder metallurgy technology. Due to its advantages of high strength, high hardness and good wear resistance, cemented carbide is widely used in many fields such as tool manufacturing, die industry and part processing.
[0003] Compared with other binding metals, nickel-based materials have attracted wide attention due to their excellent fatigue resistance, higher corrosion resistance and higher high-temperature resistance. For example, Chinese Patent CN113584338B discloses a tungsten carbide-based composite material and a preparation method thereof. This method uses tungsten carbide and metal phase as raw materials, and is formulated according to the metal phase mass fraction in the tungsten carbide-based composite material being 1-6wt%. Among them, the metal phase is metal nickel or metal cobalt; the prepared raw materials are added to a ball mill for ball milling to make the tungsten carbide and the metal phase fully mixed and uniform; the mixed material is pressed into a block under a pressure of 20-40 Mpa and placed in a graphite mold; the graphite mold is placed in a vacuum hot press furnace and prepared by vacuum hot pressing sintering to obtain a tungsten carbide-based composite material. The prepared material has good toughness and excellent comprehensive performance. However, the low wettability of Ni on the WC surface and the low solubility of WC in Ni reduce the sinterability and mechanical properties of sintered cemented carbide. As a result, compared with WC-Co cemented carbide, WC-Ni cemented carbide has poor mechanical properties, insufficient wear resistance and general corrosion resistance. Summary of the Invention
[0004] In order to solve the problems mentioned in the above background art, the present invention provides a high-strength cemented carbide tool matrix material and a preparation method thereof. The specific technical solutions are as follows: A preparation method of a high-strength cemented carbide tool matrix material, comprising the following steps: Step S1: Treat tungsten carbide with a nickel precursor solution to obtain nickel-coated tungsten carbide; Step S2: Add nickel-coated tungsten carbide, lanthanum powder, and chromium carbide powder to absolute ethanol, ball mill, dry, grind, and screen to obtain a composite powder; Step S3: Treat the composite powder with MXene material, and use ball milling combined with surfactant-assisted hydrothermal method to obtain a modified composite powder; Step S4: Add the modified composite powder, molybdenum powder, and tantalum nitride to absolute ethanol, ball mill, dry, grind, and screen to obtain a premix; Step S5: The premix is made into a green compact by dry pressing, and then cold isostatic pressing is carried out to form a blank. Finally, it is sintered by microwave to obtain cemented carbide. Step S6: The functionalized coating is sprayed on the surface of the cemented carbide, heat-treated and cured to obtain a high-strength cemented carbide tool substrate material.
[0005] Preferably, the functionalized coating is first obtained by a precipitation reaction of zinc sulfate heptahydrate and ammonium bicarbonate to obtain basic zinc carbonate, then coated with aluminum hydroxide obtained by hydrolysis of ammonium aluminum sulfate, thermally decomposed to obtain a modifier, and then complexed with dopamine and aluminum nitrate nonahydrate to obtain a functionalized filler. Finally, it is cross-linked with hydroxypropyl-terminated polydimethylsiloxane to obtain the functionalized coating.
[0006] Preferably, in step S1, the nickel-coated tungsten carbide is specifically prepared by the following steps: The nickel precursor solution is added to the tungsten carbide powder, first evaporated, and then placed in an argon atmosphere and heated to 480-520 °C at a heating rate of 5-10 °C / min to obtain nickel-coated tungsten carbide, wherein the nickel content in the nickel-coated tungsten carbide is 12-16 wt%. The nickel precursor solution is obtained by mixing nickel nitrate hexahydrate, nickel acetate tetrahydrate, triethanolamine and modified silica sol in a mass ratio of (8.5-9.5):1:(0.3-0.5):(2.8-3.4).
[0007] Preferably, in step S2, the mass ratio of nickel-coated tungsten carbide, lanthanum powder, and chromium carbide powder is (83-84):(0.12-0.16):(0.8-1.2); drying conditions: drying at 76-84 °C for 3-4 h; sieving mesh number: 200-220 mesh; ball milling conditions: ball-to-material ratio of (3-5):1, solid-to-liquid ratio of 1:(4-8), ball rotation speed of 40-50 rpm, ball milling time of 48-68 h, grinding time of 12-20 min.
[0008] Preferably, in step S3, the modified composite powder is specifically prepared by the following steps: Cetyltrimethylammonium bromide and the composite powder are added to deionized water, stirred evenly at room temperature, then MXene material is added, and stirring is continued for 60-90 min. Then ammonia water is added dropwise, and the addition is controlled to be completed within 10 min. After the addition is completed, stirring reaction is continued for 20-40 min, and the temperature is raised to 170-180 °C and stirring reaction is carried out for 22-26 h. Then it is cooled to room temperature, filtered, centrifuged, washed, and dried to obtain the modified composite powder, wherein the mass ratio of cetyltrimethylammonium bromide, the composite powder, deionized water, MXene material, and ammonia water is (7.6-12.8):(9-16):(320-460):(0.08-0.14):(5-10).
[0009] Preferably, the mass fraction of the ammonia water is 0.6 - 0.8%.
[0010] Preferably, in the step S4, the mass ratio of the modified composite powder, molybdenum powder and tantalum nitride is (84 - 86):0.8:(1.2 - 2.2); drying conditions: drying at 80 - 90 °C for 2.6 - 3.2 h; grinding time is 8 - 16 min; ball milling conditions: ball milling speed is 240 - 320 rpm, ball milling time is 2 - 3 h, ball-to-material ratio is (6 - 8):1, solid-to-liquid ratio is 1:(5 - 7).
[0011] Preferably, in the step S5, the cold isostatic pressing method is specifically as follows: the pressure is increased to 200 - 300 MPa within 3 - 5 min and the pressure is maintained for 3 - 5 min.
[0012] Preferably, in the step S5, the microwave sintering is specifically as follows: in an argon atmosphere, the temperature is raised from room temperature to 920 - 1060 °C at a heating rate of 3 - 5 °C / min and held for 12 - 18 min, and then the temperature is raised to 1420 - 1500 °C at a heating rate of 15 - 20 °C / min and held for 12 - 16 min, and then naturally cooled to room temperature.
[0013] Preferably, in the step S6, the spraying thickness of the functionalized coating is 100 - 120 µm; heat treatment method: heat treatment is carried out at 120 - 130 °C and 160 - 180 °C for 60 - 80 min successively.
[0014] Preferably, the MXene material is prepared by the following steps: Immerse the aluminum carbonitride powder in the hydrofluoric acid solution, seal it, place it in a ventilated environment and raise the temperature to 35 - 45 °C, stir and react for 18 - 24 h. After the reaction, cool it to room temperature, remove the upper clear liquid, wash it, dry it, grind and sieve it, and then place it in hydrofluoric acid and stir for 24 - 48 h to obtain the MXene material, wherein the mass ratio of the aluminum carbonitride powder, hydrofluoric acid solution and hydrofluoric acid is (1 - 2):(20 - 30):(10 - 14). In the above reaction process, the MXene material is prepared through the etching - peeling - purification process.
[0015] Preferably, the mass fraction of the hydrofluoric acid solution is 35 - 45%.
[0016] Preferably, the modified silica sol is made by the following steps: Mix tetraethyl orthosilicate and absolute ethanol, adjust the pH value to 4 - 5 while stirring at 30 - 40°C, react for 2 - 4 h, add aluminum dihydrogen phosphate solution, stir and react at 50 - 70°C for 4 - 6 h to obtain modified silica sol. Among them, the mass ratio of tetraethyl orthosilicate, absolute ethanol and aluminum dihydrogen phosphate solution is (16 - 18):(5.5 - 6.5):(14 - 16). During the above reaction process, absolute ethanol is the solvent, and aluminum dihydrogen phosphate can catalyze the hydrolysis and condensation reaction of tetraethyl orthosilicate to obtain modified silica sol.
[0017] Preferably, the mass fraction of the aluminum dihydrogen phosphate solution is 32 - 36%.
[0018] Preferably, the preparation method of the functionalized coating includes the following steps: Step A1: Dissolve zinc sulfate heptahydrate in deionized water, add ammonium bicarbonate aqueous solution, and while stirring, dropwise add the mixed solution a of ammonium aluminum sulfate and deionized water, and control to finish dropping within 15 min. After dropping, raise the temperature to 54 - 60°C, stir and react for 0.4 - 0.6 h, filter, wash and dry to obtain a modifier. Among them, the mass ratio of zinc sulfate heptahydrate, deionized water, ammonium bicarbonate aqueous solution and mixed solution a is (60 - 70):300:(290 - 300):(70 - 80). In the mixed solution a, the mass ratio of ammonium aluminum sulfate and deionized water is 1:(8 - 9), and the mass fraction of the ammonium bicarbonate aqueous solution is 13.2 - 13.6%. During the above process, the aluminum hydroxide colloid obtained by the hydrolysis of ammonium aluminum sulfate has a large specific surface area and strong adsorption ability, and can interact with the surface of zinc oxide to form a stable coating structure, and a modifier with aluminum hydroxide coated on the surface is obtained; Step A2: Ultrasonically disperse the modifier in Tris - HC1 buffer solution with a pH of 8 - 9, then add dopamine, stir and react for 3 - 5 h, and then add aluminum nitrate nonahydrate, and continue to stir for 3.5 - 4.5 h. After centrifugation and washing, a functionalized filler is obtained. Among them, the mass ratio of the modifier, Tris - HC1 buffer solution, dopamine and aluminum nitrate nonahydrate is (2 - 3):(45 - 55):(0.7 - 1.1):(0.2 - 0.5); Step A3: Add aluminum dihydrogen phosphate and the functionalized filler to anhydrous DMF, raise the temperature to 55 - 65°C, stir evenly, and then dropwise add the mixed solution b of hydroxypropyl - terminated polydimethylsiloxane and toluene, and control to finish dropping within 15 min. After dropping, raise the temperature to 75 - 85°C, and continue to stir for 12 - 16 min to obtain a functionalized coating. Among them, the mass ratio of aluminum dihydrogen phosphate, functionalized filler, anhydrous DMF and mixed solution b is (35 - 45):(6 - 10):(80 - 100):(16 - 22). In the mixed solution b, the mass ratio of hydroxypropyl - terminated polydimethylsiloxane and toluene is (3 - 5):20.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention starts from two aspects: optimizing the composition of the alloy and coating with a functionalized coating, combining internal and external factors to obtain a cemented carbide tool matrix material with excellent wear resistance, corrosion resistance and toughness. Specifically: 1. During the alloy preparation process, nano-nickel is deposited and coated on the surface of tungsten carbide by the solution method combined with modified silica sol. At the same time, the hydroxyl groups of silica nanoparticles in the silica sol and the phosphate groups on the surface of aluminum dihydrogen phosphate can serve as anchor groups to bind nano-nickel through multi-point adsorption, forming uniform nucleation sites. Aluminum dihydrogen phosphate can also catalyze the hydrolysis and condensation reaction of tetraethyl orthosilicate, improving the deposition effect of nano-nickel. Compared with the traditional method of directly adding nickel, it can improve the poor wettability of nickel on the surface of tungsten carbide, making the nickel in the binder phase evenly distributed on the surface of tungsten carbide, improving the sinterability of nickel-coated tungsten carbide, increasing the density of the alloy, and improving the hardness and corrosion resistance of the alloy while maintaining the toughness of the alloy; the addition of lanthanum metal powder reacts with impurities such as oxygen and sulfur in the alloy to form stable compounds, changing the distribution state of impurities, reducing interfacial segregation, increasing the bonding strength of the alloy matrix interface, and enhancing mechanical properties and wear resistance; tungsten carbide replaces chromium metal in the traditional process. On the one hand, it can increase the carbon content in the raw materials, prevent the decarburization effect of oxygen elements in rare earth oxides on cemented carbide, and prevent problems such as product cracking during sintering, ensuring the structural stability of the alloy, thus ensuring the original bending strength and corrosion resistance of the alloy. On the other hand, it also prevents the formation of a large amount of nickel-chromium alloy in the alloy from damaging the original structure of the alloy and reducing the performance of the alloy. In addition, the MXene material is prepared by an etching-stripping process. The addition of the MXene material not only significantly inhibits the growth of tungsten carbide grains, and grain refinement helps to improve the hardness and toughness of the alloy, but also the addition of the MXene material can form a dense oxide layer on the surface of the alloy, improving the corrosion resistance of the alloy; in addition, tantalum nitride plays a role in refining grains and precipitation strengthening, increasing the hardness and wear resistance of the alloy; and during the sintering process, tantalum nitride decomposes and reacts with nickel to generate free nitrogen. The generation of free nitrogen can promote grain growth, and together with tantalum nitride and chromium carbide, it prevents the grains from being too small and reasonably adjusts the grain size.
[0020] 2. The present invention covalently links a modifier, dopamine, and hydroxypropyl-terminated polydimethylsiloxane to form an organic-inorganic three-dimensional crosslinked network: the lamellar structure of aluminum hydroxide on the outer layer of the modifier combines with the spherical structure of nano-zinc oxide. The lamellar structure blocks the straight through-holes in the coating and can play a lubricating role. The spherical nano-zinc oxide not only has high hardness but also can further fill the micropores between the coating and the alloy substrate. At the same time, it can form a dense oxide layer on the surface of the alloy substrate, improving the wear resistance and corrosion resistance of the coating; the abundant hydroxyl groups in the organic-inorganic three-dimensional crosslinked network structure enable the coating to directly form a strong binding force with the alloy substrate, improving the adhesion of the coating; in addition, the polydopamine in the present invention can form a stable hydrogen bond interaction with the modifier, improving the dispersibility of the modifier in the functional coating and the binding strength with hydroxypropyl-terminated polydimethylsiloxane, improving the corrosion resistance and wear resistance of the coating; in addition, both polydopamine and alumina are excellent corrosion inhibitors, which can delay or prevent metal corrosion, realizing active anti-corrosion. Combined with the physical barrier and chemical anti-corrosion of hydroxypropyl-terminated polydimethylsiloxane, a better anti-corrosion effect is achieved. Detailed implementation manners
[0021] To make the implementation manners of the present invention easier to understand, the present invention will be described in detail below in conjunction with specific examples. These examples are only illustrative and are not limited to the application scope of the present invention.
[0022] For those not specifying specific techniques or conditions in the examples, they shall be in accordance with the techniques or conditions described in the literature in this field or in accordance with the product specifications. For the reagents or instruments not indicating the manufacturer, they are all conventional products that can be obtained through regular channels.
[0023] The aluminum dihydrogen phosphate is the Jinshuo brand liquid industrial-grade aluminum dihydrogen phosphate sold by Zhengzhou Jinshuo Thermal Insulation and Refractory Materials Co., Ltd. The hydroxypropyl-terminated polydimethylsiloxane is produced by Guangdong Wengjiang Chemical Reagent Co., Ltd., and the CAS number is 104780-66-7.
[0024] The present invention will be further described in detail below in conjunction with examples and comparative examples.
[0025] Preparation Examples 1-3 and Comparative Preparation Example 1 provide the preparation methods of modified silica sols.
[0026] Preparation Example 1 This preparation example provides a modified silica sol, which is made by the following steps: TEOS and absolute ethanol were stirred at 600 rpm for 14 min until homogeneous. The rotation speed was maintained unchanged at 30 °C, and the pH value was adjusted to 4 with 0.6 M hydrochloric acid aqueous solution while stirring. The reaction was carried out for 2 h, and an aluminum dihydrogen phosphate solution with a mass fraction of 32% was added. The reaction was continued with stirring at 50 °C for 4 h to obtain a modified silica sol. Among them, the mass ratio of TEOS, absolute ethanol, and aluminum dihydrogen phosphate solution was 16:5.5:14.
[0027] Preparation Example 2 This preparation example provides a modified silica sol, which is prepared by the following steps: TEOS and absolute ethanol were stirred at 650 rpm for 16 min until homogeneous. The rotation speed was maintained unchanged at 35 °C, and the pH value was adjusted to 4.5 with 0.8 M hydrochloric acid aqueous solution while stirring. The reaction was carried out for 3 h, and an aluminum dihydrogen phosphate solution with a mass fraction of 34% was added. The reaction was continued with stirring at 60 °C for 5 h to obtain a modified silica sol. Among them, the mass ratio of TEOS, absolute ethanol, and aluminum dihydrogen phosphate solution was 17:6.0:15.
[0028] Preparation Example 3 This preparation example provides a modified silica sol, which is prepared by the following steps: TEOS and absolute ethanol were stirred at 700 rpm for 18 min until homogeneous. The rotation speed was maintained unchanged at 40 °C, and the pH value was adjusted to 5 with 1.0 M hydrochloric acid aqueous solution while stirring. The reaction was carried out for 4 h, and an aluminum dihydrogen phosphate solution with a mass fraction of 36% was added. The reaction was stirred at 70 °C for 6 h to obtain a modified silica sol. Among them, the mass ratio of TEOS, absolute ethanol, and aluminum dihydrogen phosphate solution was 18:6.5:16.
[0029] Comparative Preparation Example 1 This comparative preparation example provides a modified silica sol, which is prepared by the following steps: TEOS and absolute ethanol were stirred at 600 rpm for 14 min until homogeneous. The rotation speed was maintained unchanged at 30 °C, and the pH value was adjusted to 4 with 0.6 M hydrochloric acid aqueous solution while stirring. The reaction was carried out for 2 h, and an aqueous solution of silane coupling agent KH-560 with a mass fraction of 32% was added. The reaction was continued with stirring at 50 °C for 4 h to obtain a modified silica sol. Among them, the mass ratio of TEOS, absolute ethanol, and aqueous solution of silane coupling agent KH-560 was 16:5.5:14.
[0030] Preparation Examples 4-6 and Comparative Preparation Example 2 provide an MXene material.
[0031] Preparation Example 4 This preparation example provides an MXene material, which is prepared by the following steps: Immerse aluminum carbide-titanium powder in a hydrofluoric acid solution with a mass fraction of 35%, seal it, place it in a ventilated environment and heat it to 35°C, stir and react at a rotation speed of 550 rpm for 18 h. After the reaction is completed, cool it to room temperature, remove the upper clear liquid, wash it with deionized water until neutral, dry it at 75°C to constant weight, grind it through a 300-mesh sieve, and then place it in hydrofluoric acid and stir for 24 h to obtain the MXene material. Among them, the mass ratio of aluminum carbide-titanium powder, hydrofluoric acid solution and hydrofluoric acid is 1:20:10.
[0032] Preparation Example 5 This preparation example provides an MXene material, which is prepared by the following steps: Immerse aluminum carbide-titanium powder in a hydrofluoric acid solution with a mass fraction of 40%, seal it, place it in a ventilated environment and heat it to 40°C, stir and react at a rotation speed of 600 rpm for 21 h. After the reaction is completed, cool it to room temperature, remove the upper clear liquid, wash it with deionized water until neutral, dry it at 80°C to constant weight, grind it through a 350-mesh sieve, and then place it in hydrofluoric acid and stir for 36 h to obtain the MXene material. Among them, the mass ratio of aluminum carbide-titanium powder, hydrofluoric acid solution and hydrofluoric acid is 1.5:25:12.
[0033] Preparation Example 6 This preparation example provides an MXene material, which is prepared by the following steps: Immerse aluminum carbide-titanium powder in a hydrofluoric acid solution with a mass fraction of 45%, seal it, place it in a ventilated environment and heat it to 45°C, stir and react at a rotation speed of 650 rpm for 24 h. After the reaction is completed, cool it to room temperature, remove the upper clear liquid, wash it with deionized water until neutral, dry it at 85°C to constant weight, grind it through a 400-mesh sieve, and then place it in hydrofluoric acid and stir for 48 h to obtain the MXene material. Among them, the mass ratio of aluminum carbide-titanium powder, hydrofluoric acid solution and hydrofluoric acid is 2:30:14.
[0034] Comparative Preparation Example 2 This comparative preparation example provides an MXene material, which is prepared by the following steps: Immerse aluminum carbide-titanium powder in a hydrofluoric acid solution with a mass fraction of 35%, seal it, place it in a ventilated environment and heat it to 35°C, stir and react at a rotation speed of 550 rpm for 18 h. After the reaction is completed, cool it to room temperature, remove the upper clear liquid, wash it with deionized water until neutral, dry it at 75°C to constant weight, grind it through a 300-mesh sieve, and then place it in deionized water and stir for 24 h to obtain the MXene material. Among them, the mass ratio of aluminum carbide-titanium powder, hydrofluoric acid solution and hydrofluoric acid is 1:20:10.
[0035] Preparation Examples 7-9 and Comparative Preparation Examples 3-5 provide a preparation method of a functional coating.
[0036] Preparation Example 7 This preparation example provides a method for preparing a functionalized coating. The method for preparing the functionalized coating includes the following steps: Step A1: Dissolve zinc sulfate heptahydrate in deionized water, add an aqueous ammonium bicarbonate solution, and while stirring, dropwise add a mixed solution a of ammonium aluminum sulfate and deionized water. Control the dropping to be completed within 15 minutes. After dropping, raise the temperature to 54°C and stir and react at a rotation speed of 600 rpm for 0.4 h. Filter, wash 3 times with deionized water, and dry to constant weight at 110°C to obtain a modifier. Among them, the mass ratio of zinc sulfate heptahydrate, deionized water, aqueous ammonium bicarbonate solution, and mixed solution a is 60:300:290:70. In the mixed solution a, the mass ratio of ammonium aluminum sulfate to deionized water is 1:8, and the mass fraction of the aqueous ammonium bicarbonate solution is 13.2%; Step A2: Ultrasonically disperse the modifier in a Tris-HCl buffer solution with a pH of 8. Control the ultrasonic frequency to be 35 kHz, the ultrasonic power to be 550 w, and ultrasonic for 22 minutes. Then add dopamine and stir and react at a rotation speed of 720 rpm for 3 h. Then add aluminum nitrate nonahydrate, maintain the rotation speed unchanged, and continue to stir for 3.5 h. After centrifugation, wash 3 times with anhydrous ethanol and deionized water in sequence to obtain a functionalized filler. Among them, the mass ratio of the modifier, Tris-HCl buffer solution, dopamine, and aluminum nitrate nonahydrate is 2:45:0.7:0.2; Step A3: Add aluminum dihydrogen phosphate and the functionalized filler to anhydrous DMF, raise the temperature to 55°C, stir at a rotation speed of 700 rpm for 12 minutes until uniform, then dropwise add a mixed solution b of hydroxypropyl-terminated polydimethylsiloxane and toluene. Control the dropping to be completed within 15 minutes. After dropping, raise the temperature to 75°C, maintain the rotation speed unchanged, and continue to stir for 12 minutes to obtain a functionalized coating. Among them, the mass ratio of aluminum dihydrogen phosphate, functionalized filler, anhydrous DMF, and mixed solution b is 35:6:80:16. In the mixed solution b, the mass ratio of hydroxypropyl-terminated polydimethylsiloxane to toluene is 3:20.
[0037] Preparation Example 8 This preparation example provides a method for preparing a functionalized coating. The method for preparing the functionalized coating includes the following steps: Step A1: Dissolve zinc sulfate heptahydrate in deionized water, add ammonium bicarbonate aqueous solution, and dropwise add the mixed solution a of ammonium aluminum sulfate and deionized water while stirring. Control the dropping to be completed within 15 min. After dropping, raise the temperature to 57 °C, stir and react at a rotation speed of 650 rpm for 0.4 h, filter, wash 4 times with deionized water, and dry to constant weight at 115 °C to obtain a modifier. Among them, the mass ratio of zinc sulfate heptahydrate, deionized water, ammonium bicarbonate aqueous solution, and mixed solution a is 60:300:290:70. In the mixed solution a, the mass ratio of ammonium aluminum sulfate to deionized water is 1:8, and the mass fraction of the ammonium bicarbonate aqueous solution is 13.4%; Step A2: Ultrasonically disperse the modifier in a Tris-HCl buffer solution with a pH of 8.5. Control the ultrasonic frequency to be 40 kHz, the ultrasonic power to be 600 w, and ultrasonic for 24 min. Then add dopamine, stir and react for 4 h, then add aluminum nitrate nonahydrate, and continue to stir for 4.0 h. After centrifugation, wash 4 times with absolute ethanol and deionized water in sequence to obtain a functionalized filler. Among them, the mass ratio of the modifier, Tris-HCl buffer solution, dopamine, and aluminum nitrate nonahydrate is 2.5:50:0.9:0.35; Step A3: Add aluminum dihydrogen phosphate and the functionalized filler to anhydrous DMF, raise the temperature to 60 °C, stir at a rotation speed of 740 rpm for 26 min, then dropwise add the mixed solution b of hydroxypropyl-terminated polydimethylsiloxane and toluene. Control the dropping to be completed within 15 min. After dropping, raise the temperature to 80 °C, keep the rotation speed unchanged, and continue to stir for 14 min to obtain a functionalized coating. Among them, the mass ratio of aluminum dihydrogen phosphate, the functionalized filler, anhydrous DMF, and mixed solution b is 40:8:90:19. In the mixed solution b, the mass ratio of hydroxypropyl-terminated polydimethylsiloxane to toluene is 4:20 Dissolve hydroxypropyl-terminated polydimethylsiloxane in absolute ethanol, then add the functionalized filler, raise the temperature to 55 °C, stir at a rotation speed of 740 rpm for 14 min to obtain a functionalized coating. Among them, the mass ratio of hydroxypropyl-terminated polydimethylsiloxane, absolute ethanol, and the functionalized filler is 5:19:0.8.
[0038] Preparation Example 9 This preparation example provides a method for preparing a functionalized coating. The method for preparing the functionalized coating includes the following steps: Step A1: Dissolve zinc sulfate heptahydrate in deionized water, add an aqueous solution of ammonium bicarbonate, and while stirring, dropwise add a mixed solution a of ammonium aluminum sulfate and deionized water. Control to finish dropping within 15 minutes. After dropping, raise the temperature to 60 °C, stir and react at a rotation speed of 700 rpm for 0.6 h, filter, wash with deionized water 5 times, and dry at 120 °C to constant weight to obtain a modifier. Among them, the mass ratio of zinc sulfate heptahydrate, deionized water, aqueous ammonium bicarbonate solution, and mixed solution a is 70:300:300:80. In the mixed solution a, the mass ratio of ammonium aluminum sulfate to deionized water is 1:9, and the mass fraction of the aqueous ammonium bicarbonate solution is 13.6%; Step A2: Ultrasonically disperse the modifier in a Tris-HCl buffer solution with a pH of 9. Control the ultrasonic frequency to be 45 kHz, the ultrasonic power to be 650 w, and ultrasonicate for 26 minutes. Then add dopamine, stir and react for 5 h. Then add aluminum nitrate nonahydrate and continue to stir for 4.5 h. After centrifugation, wash with absolute ethanol and deionized water 5 times in sequence to obtain a functionalized filler. Among them, the mass ratio of the modifier, Tris-HCl buffer solution, dopamine, and aluminum nitrate nonahydrate is 3:55:1.1:0.5; Step A3: Add aluminum dihydrogen phosphate and the functionalized filler to anhydrous DMF, raise the temperature to 65 °C, stir at a rotation speed of 780 rpm for 30 minutes until uniform, then dropwise add a mixed solution b of hydroxylpropyl-terminated polydimethylsiloxane and toluene. Control to finish dropping within 15 minutes. After dropping, raise the temperature to 85 °C, maintain the rotation speed unchanged, and continue to stir for 16 minutes to obtain a functionalized coating. Among them, the mass ratio of aluminum dihydrogen phosphate, functionalized filler, anhydrous DMF, and mixed solution b is 45:10:100:22. In the mixed solution b, the mass ratio of hydroxylpropyl-terminated polydimethylsiloxane to toluene is 5:20.
[0039] Comparative Preparation Example 3 This comparative preparation example provides a method for preparing a functionalized coating. The method for preparing the functionalized coating includes the following steps: Step A1: Dissolve copper sulfate in deionized water, add an aqueous solution of ammonium bicarbonate, and while stirring, dropwise add a mixed solution a of ammonium aluminum sulfate and deionized water. Control to finish dropping within 15 minutes. After dropping, raise the temperature to 54 °C, stir and react at a rotation speed of 600 rpm for 0.4 h, filter, wash with deionized water 3 times, and dry at 110 °C to constant weight to obtain a modifier. Among them, the mass ratio of copper sulfate, deionized water, aqueous ammonium bicarbonate solution, and mixed solution a is 60:300:290:70. In the mixed solution a, the mass ratio of ammonium aluminum sulfate to deionized water is 1:8, and the mass fraction of the aqueous ammonium bicarbonate solution is 13.2%; Step A2: Ultrasonically disperse the modifier in Tris-HC1 buffer solution with a pH of 8. Control the ultrasonic frequency at 35 kHz, ultrasonic power at 550 W, and ultrasonicate for 22 min. Then add dopamine and stir and react at a rotation speed of 720 rpm for 3 h. Next, add aluminum nitrate nonahydrate, maintain the rotation speed unchanged, and continue stirring for 3.5 h. After centrifugation, wash three times with anhydrous ethanol and deionized water successively to obtain functionalized filler. Among them, the mass ratio of the modifier, Tris-HC1 buffer solution, dopamine, and aluminum nitrate nonahydrate is 2:45:0.7:0.2; Step A3: Add aluminum dihydrogen phosphate and functionalized filler into anhydrous DMF, heat up to 55 °C, stir at a rotation speed of 700 rpm for 12 min until homogeneous, then dropwise add mixture b of hydroxypropyl-terminated polydimethylsiloxane and toluene, control to finish dropping within 15 min. After dropping, heat up to 75 °C, maintain the rotation speed unchanged, and continue stirring for 12 min to obtain functionalized coating. Among them, the mass ratio of aluminum dihydrogen phosphate, functionalized filler, anhydrous DMF, and mixture b is 35:6:80:16. In mixture b, the mass ratio of hydroxypropyl-terminated polydimethylsiloxane and toluene is 3:20.
[0040] Comparative Preparation Example 4 This comparative preparation example provides a preparation method of a functionalized coating. The preparation method of this functionalized coating includes the following steps: Step A1: Dissolve zinc sulfate heptahydrate in deionized water, add ammonium bicarbonate aqueous solution, and while stirring, dropwise add mixture a of ammonium copper sulfate and deionized water, control to finish dropping within 15 min. After dropping, heat up to 54 °C, stir and react at a rotation speed of 600 rpm for 0.4 h, filter, wash three times with deionized water, and dry at 110 °C to constant weight to obtain the modifier. Among them, the mass ratio of zinc sulfate heptahydrate, deionized water, ammonium bicarbonate aqueous solution, and mixture a is 60:300:290:70. In mixture a, the mass ratio of ammonium copper sulfate and deionized water is 1:8, and the mass fraction of the ammonium bicarbonate aqueous solution is 13.2%; Step A2: Ultrasonically disperse the modifier in Tris-HC1 buffer solution with a pH of 8. Control the ultrasonic frequency at 35 kHz, ultrasonic power at 550 W, and ultrasonicate for 22 min. Then add dopamine and stir and react at a rotation speed of 720 rpm for 3 h. Next, add aluminum nitrate nonahydrate, maintain the rotation speed unchanged, and continue stirring for 3.5 h. After centrifugation, wash three times with anhydrous ethanol and deionized water successively to obtain functionalized filler. Among them, the mass ratio of the modifier, Tris-HC1 buffer solution, dopamine, and aluminum nitrate nonahydrate is 2:45:0.7:0.2; Step A3: Add aluminum dihydrogen phosphate and functionalized filler into anhydrous DMF, heat up to 55°C, stir for 12 min at a rotation speed of 700 rpm until homogeneous, then dropwise add mixture b of hydroxypropyl-terminated polydimethylsiloxane and toluene, control to finish dropping within 15 min. After dropping, heat up to 75°C, keep the rotation speed unchanged, and continue to stir for 12 min to obtain the functionalized coating. Among them, the mass ratio of aluminum dihydrogen phosphate, functionalized filler, anhydrous DMF and mixture b is 35:6:80:16. In mixture b, the mass ratio of hydroxypropyl-terminated polydimethylsiloxane and toluene is 3:20.
[0041] Comparative Preparation Example 5 This comparative preparation example provides a preparation method of a functionalized coating. The preparation method of this functionalized coating includes the following steps: Step A1: Dissolve zinc sulfate heptahydrate in deionized water, add ammonium bicarbonate aqueous solution, while stirring, dropwise add mixture a of ammonium aluminum sulfate and deionized water, control to finish dropping within 15 min. After dropping, heat up to 54°C, stir and react at a rotation speed of 600 rpm for 0.4 h, filter, wash with deionized water 3 times, and dry at 110°C to constant weight to obtain the modifier. Among them, the mass ratio of zinc sulfate heptahydrate, deionized water, ammonium bicarbonate aqueous solution and mixture a is 60:300:290:70. In mixture a, the mass ratio of ammonium aluminum sulfate and deionized water is 1:8, and the mass fraction of ammonium bicarbonate aqueous solution is 13.2%; Step A2: Ultrasonically disperse the modifier in Tris-HCl buffer solution with a pH of 8, control the ultrasonic frequency to be 35 kHz, the ultrasonic power to be 550 w, ultrasonic for 22 min, then add dopamine, stir and react at a rotation speed of 720 rpm for 3 h, then add cerium nitrate, keep the rotation speed unchanged, and continue to stir for 3.5 h. After centrifugation, wash with anhydrous ethanol and deionized water 3 times in sequence to obtain the functionalized filler. Among them, the mass ratio of the modifier, Tris-HCl buffer solution, dopamine and cerium nitrate is 2:45:0.7:0.2; Step A3: Add aluminum dihydrogen phosphate and functionalized filler into anhydrous DMF, heat up to 55°C, stir for 12 min at a rotation speed of 700 rpm until homogeneous, then dropwise add mixture b of hydroxypropyl-terminated polydimethylsiloxane and toluene, control to finish dropping within 15 min. After dropping, heat up to 75°C, keep the rotation speed unchanged, and continue to stir for 12 min to obtain the functionalized coating. Among them, the mass ratio of aluminum dihydrogen phosphate, functionalized filler, anhydrous DMF and mixture b is 35:6:80:16. In mixture b, the mass ratio of hydroxypropyl-terminated polydimethylsiloxane and toluene is 3:20.
[0042] Examples 1-3 and Comparative Examples 1-5 provide a preparation method of a high-strength cemented carbide tool substrate material.
[0043] Example 1 This example provides a method for preparing a high-strength cemented carbide tool matrix material, including the following steps: Step S1: Add the nickel precursor solution to the tungsten carbide powder, first evaporate it, and then place it in an argon atmosphere. Heat it to 480 °C at a heating rate of 5 °C / min to obtain nickel-coated tungsten carbide, where the nickel content in the nickel-coated tungsten carbide is 12 wt%. The nickel precursor solution is obtained by mixing nickel nitrate hexahydrate, nickel acetate tetrahydrate, triethanolamine, and the modified silica sol prepared in Preparation Example 1 in a mass ratio of 8.5:1:0.3:2.8; Step S2: Add the nickel-coated tungsten carbide, lanthanum powder, and chromium carbide powder to anhydrous ethanol, ball mill, control the ball-to-material ratio to be 3:1, the solid-to-liquid ratio to be 1:4, the ball rotation speed to be 40 rpm, and the ball milling time to be 48 h. Then dry it at 76 °C for 3 h, grind it for 12 min, and pass through a 300-mesh sieve to obtain a composite powder, where the mass ratio of the nickel-coated tungsten carbide, lanthanum powder, and chromium carbide powder is 83:0.12:0.8; Step S3: Add cetyltrimethylammonium bromide and the composite powder to deionized water, stir at a rotation speed of 600 rpm at room temperature for 12 min until uniform, then add the MXene material prepared in Preparation Example 4, keep the rotation speed unchanged, continue to stir for 60 min, then dropwise add ammonia water with a mass fraction of 0.6%, control to finish dropping within 10 min. After dropping, continue to stir and react for 20 min, heat up to 170 °C and stir and react for 22 h, cool to room temperature, centrifuge and separate, wash 3 times with deionized water, and dry at 60 °C to constant weight to obtain a modified composite powder, where the mass ratio of cetyltrimethylammonium bromide, the composite powder, deionized water, the MXene material, and ammonia water is 7.6:9:320:0.08:5; Step S4: Add the modified composite powder, molybdenum powder, and tantalum nitride to anhydrous ethanol, ball mill, control the ball milling rotation speed to be 240 rpm, the ball milling time to be 2 h, the ball-to-material ratio to be 6:1, and the solid-to-liquid ratio to be 1:5; dry, and then dry at 80 °C for 2.6 h, grind for 8 min, and pass through a 120-mesh sieve to obtain a premix, where the mass ratio of the modified composite powder, molybdenum powder, and tantalum nitride is 84:0.8:1.2; Step S5: Make the premix into a green compact by dry pressing, then raise the pressure to 20 MPa within 3 min, keep the pressure for 3 min to form a blank, and finally in an argon atmosphere, heat from room temperature to 920 °C at a heating rate of 3 °C / min and keep it warm for 12 min, then heat up to 1420 °C at a heating rate of 15 °C / min and keep it warm for 12 min, and naturally cool to room temperature to obtain cemented carbide; Step S6: Spray the functionalized coating prepared in Preparation Example 7 onto the surface of cemented carbide with a spraying thickness of 100 µm, and heat-treat it at 120 °C and 160 °C for 60 min successively, then cure to obtain the matrix material of the high-strength cemented carbide cutting tool.
[0044] Example 2 This example provides a preparation method of the matrix material of the high-strength cemented carbide cutting tool, including the following steps: Step S1: Add the nickel precursor solution to the tungsten carbide powder, first evaporate it, and then place it in an argon atmosphere and heat it to 500 °C at a heating rate of 8 °C / min to obtain nickel-coated tungsten carbide, where the nickel content in the nickel-coated tungsten carbide is 14 wt%; the nickel precursor solution is obtained by mixing nickel nitrate hexahydrate, nickel acetate tetrahydrate, triethanolamine and the modified silica sol prepared in Preparation Example 2 in a mass ratio of 9.0:1:0.4:3.1; Step S2: Add the nickel-coated tungsten carbide, lanthanum powder, and chromium carbide powder to anhydrous ethanol, ball-mill them, control the ball-to-material ratio to be 4:1, the solid-to-liquid ratio to be 1:6, the ball rotation speed to be 45 rpm, and the ball-milling time to be 58 h. Then dry it at 80 °C for 3.5 h, grind it for 16 min, and pass through a 320-mesh sieve to obtain a composite powder, where the mass ratio of the nickel-coated tungsten carbide, lanthanum powder, and chromium carbide powder is 83.5:0.14:1.0; Step S3: Add cetyltrimethylammonium bromide and the composite powder to deionized water, stir at a rotation speed of 640 rpm at room temperature for 16 min until uniform, then add the MXene material prepared in Preparation Example 5, keep the rotation speed unchanged, continue to stir for 75 min, then dropwise add ammonia water with a mass fraction of 0.7%, control to finish dropping within 10 min, after dropping, continue to stir and react for 30 min, raise the temperature to 175 °C and stir and react for 24 h, cool to room temperature, centrifuge and separate, wash 4 times with deionized water, and dry at 65 °C to constant weight to obtain a modified composite powder, where the mass ratio of cetyltrimethylammonium bromide, the composite powder, deionized water, the MXene material, and ammonia water is 10.2:12.5:390:0.11:7.5; Step S4: Add the modified composite powder, molybdenum powder, and tantalum nitride to anhydrous ethanol, ball-mill them, control the ball-milling rotation speed to be 280 rpm, the ball-milling time to be 2.5 h, the ball-to-material ratio to be 7:1, and the solid-to-liquid ratio to be 1:6. Then dry it at 85 °C for 2.9 h, grind it for 12 min, and pass through a 140-mesh sieve to obtain a premix, where the mass ratio of the modified composite powder, molybdenum powder, and tantalum nitride is 85:0.8:1.7; Step S5: The premix is made into a green compact by dry pressing, then the pressure is increased to 250 MPa within 4 min, held for 4 min to form a blank, and finally in an argon atmosphere, it is heated from room temperature to 990 °C at a heating rate of 4 °C / min and held for 15 min, then heated to 1460 °C at a heating rate of 18 °C / min and held for 14 min, and naturally cooled to room temperature to obtain cemented carbide; Step S6: The functionalized coating prepared in Preparation Example 8 is sprayed on the surface of the cemented carbide with a spraying thickness of 110 µm, and heat-treated at 125 °C and 170 °C for 70 min successively, and cured to obtain a high-strength cemented carbide tool substrate material.
[0045] Example 3 This example provides a preparation method of a high-strength cemented carbide tool substrate material, including the following steps: Step S1: The nickel precursor solution is added to the tungsten carbide powder, first evaporated, and then placed in an argon atmosphere and heated to 520 °C at a heating rate of 10 °C / min to obtain nickel-coated tungsten carbide, wherein the nickel content in the nickel-coated tungsten carbide is 16 wt%; the nickel precursor solution is obtained by mixing nickel nitrate hexahydrate, nickel acetate tetrahydrate, triethanolamine and the modified silica sol prepared in Preparation Example 3 in a mass ratio of 9.5:1:0.5:3.4; Step S2: The nickel-coated tungsten carbide, lanthanum powder and chromium carbide powder are added to anhydrous ethanol and ball-milled. The ball-to-material ratio is controlled at 5:1, the solid-to-liquid ratio is 1:8, the ball rotation speed is 50 rpm, and the ball-milling time is 68 h. Then it is dried at 84 °C for 4 h, ground for 20 min, and sieved through a 340-mesh sieve to obtain a composite powder, wherein the mass ratio of the nickel-coated tungsten carbide, lanthanum powder and chromium carbide powder is 84:0.16:1.2; Step S3: Cetyltrimethylammonium bromide and the composite powder are added to deionized water, stirred at a rotation speed of 680 rpm at room temperature for 20 min until uniform, then the MXene material prepared in Preparation Example 6 is added, and stirring is continued for 90 min. Then, ammonia water with a mass fraction of 0.8% is added dropwise, and the addition is controlled to be completed within 10 min. After the addition, stirring reaction is continued for 40 min, the temperature is raised to 180 °C and stirring reaction is carried out for 26 h, cooled to room temperature, filtered, centrifuged, washed 5 times with deionized water, and dried to constant weight at 70 °C to obtain a modified composite powder, wherein the mass ratio of cetyltrimethylammonium bromide, the composite powder, deionized water, the MXene material and ammonia water is 12.8:16:460:0.14:10; Step S4: Add the modified composite powder, molybdenum powder, and tantalum nitride into absolute ethanol, and ball mill them. Control the ball milling speed at 320 rpm, the ball milling time at 3 h, the ball-to-material ratio at 8:1, and the solid-to-liquid ratio at 1:7. Then dry them at 90 °C for 3.2 h, and pass through a 160-mesh sieve to obtain the premix. Among them, the mass ratio of the modified composite powder, molybdenum powder, and tantalum nitride is 86:0.8:2.2; Step S5: Make the premix into a green compact by dry pressing, then raise the pressure to 300 MPa within 5 min, hold the pressure for 5 min to form a compact body. Finally, in an argon atmosphere, heat it from room temperature to 1060 °C at a heating rate of 5 °C / min and hold for 18 min, then heat it to 1500 °C at a heating rate of 20 °C / min and hold for 16 min, and naturally cool it to room temperature to obtain the cemented carbide; Step S6: Spray the functionalized coating prepared in Preparation Example 9 on the surface of the cemented carbide, with a spraying thickness of 120 µm, and heat-treat it at 130 °C and 180 °C for 80 min successively, and cure it to obtain the high-strength cemented carbide tool substrate material.
[0046] Comparative Example 1 Comparative Example 1 is the same as Example 1, the only difference being that the modified silica sol in Example 1 is replaced with the modified silica sol prepared in Comparative Preparation Example 1.
[0047] Comparative Example 2 Comparative Example 2 is the same as Example 1, the only difference being that the MXene material in Example 1 is replaced with the modified silica sol prepared in Comparative Preparation Example 2.
[0048] Comparative Example 3 Comparative Example 3 is the same as Example 1, the only difference being that the functionalized coating in Example 1 is replaced with the functionalized coating prepared in Comparative Preparation Example 3.
[0049] Comparative Example 4 Comparative Example 4 is the same as Example 1, the only difference being that the functionalized coating in Example 1 is replaced with the functionalized coating prepared in Comparative Preparation Example 4.
[0050] Comparative Example 5 Comparative Example 5 is the same as Example 1, the only difference being that the functionalized coating in Example 1 is replaced with the functionalized coating prepared in Comparative Preparation Example 5.
[0051] Performance Test Perform the following performance tests on the cemented carbide tool substrate materials prepared in Examples 1-3 and Comparative Examples 1-5, and control the thickness of the cemented carbide tool at 3 mm; Flexural strength: Test according to GB / T232-2010, and use the three-point bending method to test the flexural strength; Impact resistance: The prepared cemented carbide tool substrate material was used as a cutting tool to cut 42CrMo steel. The cutting speed was 250 m / min, the cutting depth was 2 mm, and the feed rate was 0.5 mm / rev. The machining length completed when obvious chipping or breakage and other defects occurred on the cutting tool was used as the evaluation criterion, with the unit of m. The larger the machining length value, the better the impact resistance of the cemented carbide; Wear resistance: The prepared cemented carbide tool substrate material was used as a cutting tool to cut 42CrMo steel. The cutting speed was 250 m / min, the cutting depth was 2 mm, and the feed rate was 0.1 mm / rev. The machining length completed when the wear amount of the cutting tool reached 0.1 mm was used as the evaluation criterion, with the unit of m. The larger the machining length value, the better the wear resistance of the cemented carbide; Vickers hardness: The room temperature hardness (HV) was measured on a Vickers hardness tester with a load of 30 kg; according to the Nihara formula, the fracture toughness (KIC) was calculated from the radial crack length generated by the Vickers hardness indentation, with the unit of MPa·m1 / 2; Corrosion resistance test: An electrochemical workstation (CHI 660E, Shanghai Chenhua Instrument Co., Ltd.) was used to study the corrosion behavior of each group of samples in 3.5% NaCl aqueous solution.
[0052] The corrosion experiment was carried out at room temperature. The working electrode used an Ag / AgCl electrode as the reference electrode and a platinum foil electrode as the counter electrode. In the range of -1.0 - 0.4 V, the scanning speed was 1 mV / s, and the corrosion potential (Ecorr) of the prepared samples was analyzed; The specific test results are as follows: Table 1 Performance test results
[0053] Compared with Comparative Examples 1 - 5, the alloy tool substrate materials prepared in Examples 1 - 3 have more excellent hardness, wear resistance and toughness.
[0054] The performance data of Example 1 and Comparative Example 1 show that when aluminum dihydrogen phosphate is used to synergistically modify silica sol and introduced into the synthesis system of cemented carbide, the hardness, toughness and corrosion resistance of the alloy are significantly improved; the phosphate groups on the surface of aluminum dihydrogen phosphate can act as anchor groups to adsorb and bind nano-nickel, forming uniform nucleation sites, which can improve the problem of poor wettability of nickel on the surface of tungsten carbide, making the nickel in the binder phase evenly distributed on the surface of tungsten carbide, improving the sinterability of nickel-coated tungsten carbide, and increasing the density of the alloy, while maintaining the toughness of the alloy, improving the hardness and corrosion resistance of the alloy.
[0055] According to the test results of Example 1 and Comparative Example 2, it can be seen that through the etching process, the MXene material can have a larger specific surface area and more active sites, which not only significantly improves the wettability of the alloy interface and enhances the interfacial bonding strength of the material, but also helps to form a dense oxide layer on the alloy surface and improve the corrosion resistance of the alloy.
[0056] According to the comparative analysis of Example 1 and Comparative Example 3, it can be seen that the spherical nano-zinc oxide inside the modifier not only has high hardness itself but also can further fill the micropores between the coating and the alloy matrix. At the same time, it can also form a dense oxide layer on the surface of the alloy matrix, improving the wear resistance and corrosion resistance of the coating.
[0057] According to the test results of Example 1 and Comparative Example 4, it can be seen that the lamellar structure of aluminum hydroxide on the outer layer of the modifier can block the straight through holes in the coating and play a lubricating role, significantly improving the wear resistance and corrosion resistance of the alloy.
[0058] According to the test results of Example 1 and Comparative Example 5, it can be seen that the alumina generated by the thermal curing of aluminum nitrate nonahydrate not only has excellent physical properties itself, but also can act as a corrosion inhibitor, significantly improving the mechanical properties and corrosion resistance of the alloy.
[0059] This specific embodiment is only an explanation of the present invention and is not a limitation thereof. Those skilled in the art can make modifications to this embodiment without creative contributions according to their needs after reading this specification, but as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A method for preparing a high-strength cemented carbide tool matrix material, characterized in that: The following steps are involved: Step S1, treating tungsten carbide with a nickel precursor solution to obtain nickel-coated tungsten carbide; Step S2, adding nickel-coated tungsten carbide, lanthanum powder, and chromium carbide powder into anhydrous ethanol, ball milling, drying, grinding, and sieving to obtain a composite powder; Step S3, treating the composite powder with MXene material, using ball milling combined with surfactant-assisted hydrothermal method to obtain modified composite powder; Step S4, adding the modified composite powder, molybdenum powder and tantalum nitride into anhydrous ethanol, ball milling, drying, grinding and sieving to obtain a premix; Step S5, forming the premix into a rough blank by dry pressing, and then performing cold isostatic pressing to form a green body, and finally performing microwave sintering to obtain a cemented carbide; Step S6, spraying the functional coating on the surface of the cemented carbide, heat treating, and curing to obtain a high-strength cemented carbide tool matrix material; The functional coating is firstly prepared by precipitation reaction of zinc sulfate heptahydrate and ammonium bicarbonate to obtain basic zinc carbonate, then coated with aluminum hydroxide obtained by hydrolysis reaction of ammonium aluminum sulfate, thermally decomposed to obtain a modifier, then complexed with dopamine and aluminum nitrate nonahydrate to obtain a functional filler, and finally cross-linked with hydroxypropyl-terminated polydimethylsiloxane to obtain the functional coating.
2. The method for preparing a high-strength cemented carbide tool matrix material according to claim 1, characterized in that: In step S1, nickel-coated tungsten carbide is specifically prepared by the following steps: A nickel precursor solution is added to tungsten carbide powder, evaporated first, and then placed in an argon atmosphere, heated to 480-520°C at a heating rate of 5-10°C / min to obtain nickel-coated tungsten carbide, wherein the nickel content in the nickel-coated tungsten carbide is 12-16wt%; the nickel precursor solution is obtained by mixing nickel nitrate hexahydrate, nickel acetate tetrahydrate, triethanolamine and modified silica sol in a mass ratio of (8.5-9.5):1:(0.3-0.5):(2.8-3.4).
3. The method for preparing a high-strength cemented carbide tool matrix material according to claim 2, characterized in that: The modified silica sol is prepared by the following steps: Mix tetraethyl orthosilicate and anhydrous ethanol, adjust the pH value to 4-5 at 30-40°C while stirring, react for 2-4 hours, add aluminum dihydrogen phosphate solution, stir and react at 50-70°C for 4-6 hours to obtain modified silica sol, wherein the mass ratio of tetraethyl orthosilicate, anhydrous ethanol and aluminum dihydrogen phosphate solution is (16-18): (5.5-6.5): (14-16).
4. The method for preparing a high-strength cemented carbide tool matrix material according to claim 1, characterized in that: In the step S2, the mass ratio of nickel-coated tungsten carbide, lanthanum powder and chromium carbide powder is (83-84): (0.12-0.16): (0.8-1.2); drying conditions: drying at 76-84°C for 3-4 hours; sieving mesh size is 200-220 mesh; ball milling conditions: ball-to-material ratio is (3-5): 1, solid-liquid ratio is 1: (4-8), ball speed is 40-50rpm, ball milling time is 48-68h, and grinding time is 12-20min.
5. The method for preparing a high-strength cemented carbide tool matrix material according to claim 1, characterized in that: In step S3, the modified composite powder is specifically prepared by the following steps: Add hexadecyltrimethylammonium bromide and composite powder into deionized water, stir evenly at room temperature, then add MXene material, continue stirring for 60-90 minutes, then add ammonia water dropwise, and control the dripping to be completed within 10 minutes. After the dripping is completed, continue stirring and reacting for 20-40 minutes, heat to 170-180°C and stir and react for 22-26 hours, cool to room temperature, filter, centrifuge, wash, and dry to obtain a modified composite powder, wherein the mass ratio of hexadecyltrimethylammonium bromide, composite powder, deionized water, MXene material, and ammonia water is (7.6-12.8):(9-16):(320-460):(0.08-0.14):(5-10).
6. The method for preparing a high-strength cemented carbide tool matrix material according to claim 5, characterized in that: The MXene material is prepared by the following steps: The aluminum titanium carbide powder is immersed in a hydrofluoric acid solution, sealed, placed in a ventilated environment and heated to 35-45°C, stirred and reacted for 18-24 hours. After the reaction is completed, the temperature is cooled to room temperature, the supernatant is removed, washed, dried, ground and sieved, and then placed in hydrofluoric acid and stirred for 24-48 hours to obtain a MXene material, wherein the mass ratio of the aluminum titanium carbide powder, the hydrofluoric acid solution and the hydrofluoric acid is (1-2): (20-30): (10-14).
7. The method for preparing a high-strength cemented carbide tool matrix material according to claim 6, characterized in that: In the step S4, the mass ratio of the modified composite powder, molybdenum powder and tantalum nitride is (84-86): 0.8: (1.2-2.2); Drying conditions: Drying at 80-90℃ for 2.6-3.2h; Grinding time is 8-16min, and the solid-liquid ratio is 1: (5-7).
8. The method for preparing a high-strength cemented carbide tool matrix material according to claim 1, characterized in that: In step S5, the cold isostatic pressing method is specifically as follows: the pressure is increased to 200-300 MPa within 3-5 minutes, and the pressure is maintained for 3-5 minutes. The microwave sintering is specifically as follows: in an argon atmosphere, the temperature is increased from room temperature to 920-1060°C at a heating rate of 3-5°C / min, and the temperature is maintained for 12-18 minutes, and then the temperature is increased to 1420-1500°C at a heating rate of 15-20°C / min and the temperature is maintained for 12-16 minutes, and then the temperature is naturally cooled to room temperature.
9. The method for preparing a high-strength cemented carbide tool matrix material according to claim 1, characterized in that: In step S6, the method for preparing the functionalized coating comprises the following steps: Step A1, dissolving zinc sulfate heptahydrate in deionized water, adding ammonium bicarbonate aqueous solution, adding a mixed solution of ammonium aluminum sulfate and deionized water dropwise while stirring, and controlling the dropping to be completed within 15 minutes. After the dropping is completed, the temperature is raised to 54-60° C., stirred for reaction for 0.4-0.6 hours, filtered, washed and dried to obtain a modifier; Step A2, ultrasonically dispersing the modifier in a Tris-HCl buffer solution with a pH of 8-9, adding dopamine, stirring for 3-5 hours, adding aluminum nitrate nonahydrate, continuing to stir for 3.5-4.5 hours, centrifuging, and washing to obtain a functionalized filler; Step A3, add aluminum dihydrogen phosphate and functionalized filler to anhydrous DMF, heat to 55-65°C, stir evenly, then dropwise add a mixture of hydroxypropyl-terminated polydimethylsiloxane and toluene b, and control the dripping to be completed within 15 minutes. After the dripping is completed, heat to 75-85°C, continue stirring for 12-16 minutes to obtain a functionalized coating.
10. A high-strength cemented carbide tool matrix material prepared by the method for preparing a high-strength cemented carbide tool matrix material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Tungsten carbide-based composite materials and their preparation methods
CN113584338B
Preparation method of ultra-coarse-grain tungsten-cobalt hard alloy
CN118726786A
High-performance nitrogen-containing hard alloy material based on vanadium-titanium rare earth carbonitride solid solution and preparation method thereof
CN119242977A
Fully-dense discontinuously-reinforced titanium matrix composites and method for manufacturing the same
US20070269331A1
Rare earth element mxenes and methods of making thereof
US20220112582A1